HUMAN SECURITY IN INTERNATIONAL LAW PERSPECTIVE - Kadarudin, Kadarudin (STIH Awang Long Samarinda, 2018)
The concept of human security began to develop along with the development of human thought about the sense of security and security for his family. The concept of human security is regarded as the most modern concept and replaces the classic concept that prioritizes the national security of a country. International law as a law governing relations between countries in its development cannot be separated from the concept of human security, because the concept of human security is used by the state as an indicator of fulfilling a sense of security for its citizens. The state is the main subject in international law, therefore when the country shifts from a paradigm of maintaining national security to safeguarding human security in carrying out its international relations or carrying out its foreign policy, then one of the objects of study in international law also changes, namely to accommodate the concept of human security. This research is a normative legal research, using a legislative and conceptual approach, then analyzed qualitatively and presented descriptively. The results show that first, international law has a very close relationship with the concept of human security, countries as the main subject in international law can carry out, respect, and fulfill the rights of their citizens in accordance with what is described in the concept of human security. Second, the concept of human security is now beginning to be used by countries in their international relations, human security is then viewed as an indicator that the country has experienced the progress of civilization where the peak is human as the main object in meeting security.